Lactobacillus reuteri ZJ617 attenuates metabolic syndrome via microbiota-derived spermidine - Yanfei Ma; Yifan Zhong; Wenjie Tang; Teresa G. Valencak; Jingliang Liu; Zhaoxi Deng; Jiangdi Mao; Daren Liu; Shanshan Wang; Yuhao Wang; Haifeng Wang (Nature Communications)
Abstract Metabolic syndrome (MetS) is a difficult-to-manage disease that poses a significant risk to human health. Here, we show that the supplementation of Lactobacillus reuteri ZJ617 ameliorates symptoms of MetS in mice induced by the high-fat diet. L. reuteri ZJ617 modulates host metabolism by interacting with the microbiome, resulting in the production of spermidine synthesized by the microbiota. L. reuteri ZJ617 serves as a source of substrates for the microbiota to synthesize spermidine, hence preventing the decline of bacteria responsible for spermidine production. Spermidine treatment mimics the metabolic effects of L. reuteri ZJ617, whereas pharmacological inhibition of spermidine biosynthesis in mice abolishes these benefits. Our findings reveal the mechanism by which L. reuteri ZJ617 alleviates MetS symptoms and provide support for its potential use as a probiotic for promoting metabolic health.